Early life family conflict, Social interactions and Carotid Artery Intima-Media Thickness in Adulthood - John-Henderson, Neha A. (Psychosom Med, 2016)
OBJECTIVE: Conflict in early life family environments is known to affect psychosocial functioning and coping styles into adulthood and is reported to negatively affect access to psychosocial resources that are critical to the management of stress. However, it remains unknown whether early life family conflict similarly affects subclinical cardiovascular disease (CVD) in adulthood. We predicted that family conflict in early life would be associated with greater mean Intima-Media thickness (IMT), a subclinical marker of CVD risk, in adulthood. METHODS: Data were collected in a community sample of 503 adults (47.4 % male, mean age: 42.8 years [SD=7.3]). Associations between family conflict in early life with IMT (assessed using B-mode ultrasound) in adulthood were examined using regression analysis. We also tested for indirect effects of early life family conflict on mean IMT through ecological momentary assessment (EMA) reports of social interactions, diversity of social roles, and perceived social support. RESULTS: Linear regression analyses adjusted for demographics and physiological risk factors showed conflict in early life associated with greater mean IMT (β=0.08, t(447)=2.13, p=0.034, R(2=)0.46). Early life conflict was significantly related to diversity of social roles, perceived social support, and EMA reports of pleasant and social conflict interactions. Significant indirect effects of early life conflict on mean IMT were observed through fewer pleasant social interactions and more frequent social conflict interactions in adulthood (β = 0.001, 95% CI, 0.0001–0.0014 and β=0.001, 95% CI, 0.0002–0.0015, respectively). CONCLUSIONS: These findings provide initial evidence that family conflict in early life heightens CVD risk in adulthood, in part by shaping the quality of adulthood social interactions.